Investigation of a multi-state outbreak of Salmonella Hvittingfoss using a web-based case reporting form - Oxenford, Christopher J; Black, Andrew P; Bell, Robert J; Munnoch, Sally A; Irwin, Melissa J; Hanson, Rachel N; Owen, Rhonda L (Communicable Diseases Intelligence, 2005)
Geographically dispersed outbreaks pose challenges for investigators due to the difficulty of collecting and collating comparable data in a timely fashion. In Australia, when cases are detected in more than one, epidemiologists in different health departments must send results of their investigations by fax or email to a coordinating site for analysis. This process can result in considerable time delays and the possibility of data transcription errors. Web–based case reporting systems which house questionnaires on a secure web site allow investigators from multiple sites to enter interview data directly into the outbreak database. NetEpi Case Manager is an open source software tool designed to assist with epidemiological investigations, analyses, and other aspects of public health practice. This system is currently being developed at the Centre for Epidemiology and Research in the New South Wales Department of Health. In 2004, OzFoodNet trialled NetEpi for the Australian Government Department of Health and Ageing to assess its usefulness as an interim outbreak case reporting system for the Biosecurity Surveillance System. The trial demonstrated the benefits of a web-based case reporting system and real-time access to collated uniform data. OzFoodNet decided to use NetEpi in future investigations of geographically dispersed outbreaks.